Naringenin ameliorates myocardial injury in STZ-induced diabetic mice by reducing oxidative stress, inflammation and apoptosis via regulating the Nrf2 and NF-κB signaling pathways - He, Yongpeng; Wang, Shuaiqi; Sun, Hao; Li, Yan; Feng, Jian (Frontiers in Cardiovascular Medicine, 2022)
Diabetes-induced myocardial damage leads to diabetic cardiomyopathy and is closely associated with the generation of oxidative stress and inflammation. Naringenin (NG) exhibits antioxidant and anti-inflammatory effects. However, whether NG has cardioprotective effects against diabetic cardiomyopathy by regulating oxidative stress and inflammation remains unknown. This study investigated the effect of NG on diabetic cardiomyopathy based on an analysis of streptozotocin (STZ)-induced type 1 diabetic mice. The results indicated that NG reduced cardiac fibrosis and cardiomyocyte apoptosis in this diabetic model, accompanied by reduced blood glucose. NG inhibited pro-inflammatory cytokines, and the level of reactive oxygen species and the expressions of nuclear factor kappa-B (NF-κB) antioxidant enzymes and nuclear factor erythroid 2-related factor 2 (Nrf2) was greatly enhanced. Furthermore, in high glucose-treated H9C2 myocardial cells, NG effectively reduced cell apoptosis by inhibiting the formation of reactive oxygen species and pro-inflammatory cytokines. NG's antioxidant and anti-inflammatory activities were mechanistically associated with NF-κB inhibition and Nrf2 activation in animal and cell experiments. Data analysis showed that NG could regulate Nrf2 and NF-κB pathways to protect against diabetes-induced myocardial damage by reducing oxidative stress and inhibiting inflammation.